Longitudinal magnetic resonance imaging of changes in lung morphology and perfusion in children with cystic fibrosis from infancy through adolescence - Wielpütz, Mark Oliver; Stahl, Mirjam; Triphan, Simon M. F.; Wucherpfennig, Lena; Leutz-Schmidt, Patricia; Gestewitz, Sonja; Steinke, Eva; Graeber, Simon Y.; Kauczor, Hans-Ulrich; Eichinger, Monika; Puderbach, Michael; Alrajab, Abdulsattar; et al. (Annals of the American Thoracic Society, 2025)
Rationale: The progression of lung changes in cystic fibrosis (CF) from infancy through adolescence remains poorly understood as a result of limited longitudinal imaging data. - - Objectives: To assess changes in lung morphology and perfusion in children with CF through the pediatric age range by longitudinal chest magnetic resonance imaging (MRI). - - Methods: 1,112 annual chest MRI scans were performed in 226 patients with CF aged 0-18 years. MRI was assessed using a validated MRI scoring system. - - Results: The MRI global score continuously increased from 5.5 ± 4.6 at infancy (0 yr) to 17.9 ± 8.5 at adolescence (12-18 yr), and the MRI morphology score increased from 5.0 ± 3.9 to 12.3 ± 6.1 (P < 0.001). Bronchiectasis/wall thickening prevalence increased from 89.1% at infancy to approximately 100% at preschool age (1-5 yr), and the subscore increased from 3.1 ± 1.9 at infancy to 6.6 ± 2.1 at adolescence (P < 0.001). Mucus plugging prevalence increased from 55.4% at infancy to 83.0% at adolescence, and the subscore increased from 1.2 ± 1.6 to 3.7 ± 2.6 in the same period (P < 0.001). Perfusion abnormalities were found in 44.4% at infancy, and increased to approximately 90% at preschool age (P < 0.001). The MRI perfusion score increased from 1.1 ± 1.6 at infancy to 5.6 ± 3.0 at adolescence (P < 0.001). Chronic Pseudomonas aeruginosa infection was associated with higher MRI scores at school age (6-11 yr; P < 0.05-0.001). - - Conclusions: This is the first study to assess longitudinal changes in lung morphology and perfusion in CF throughout the pediatric age range, providing percentiles as age-specific references for lung disease severity. Our data may facilitate the use of MRI as an endpoint in clinical trials in children with CF. - - Clinical trial registered with www.clinicaltrials.gov (NCT 00760071 and NCT 02270476).